2017
DOI: 10.3748/wjg.v23.i18.3269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleeve gastrectomy plus trunk vagotomy compared with sleeve gastrectomy on glucose metabolism in diabetic rats

Abstract: AIMTo investigate the effects of sleeve gastrectomy plus trunk vagotomy (SGTV) compared with sleeve gastrectomy (SG) in a diabetic rat model.METHODSSGTV, SG, TV and Sham operations were performed on rats with diabetes induced by high-fat diet and streptozotocin. Body weight, food intake, oral glucose tolerance test, homeostasis model assessment of insulin resistance (HOMA-IR), hepatic insulin signaling (IR, IRS1, IRS2, PI3K and AKT), oral glucose stimulated insulin secretion, GLP-1 and ghrelin were compared at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Using a retrograde tracer, Ballsmider et al confirmed that SG induced the damage of the gastric vagal nerve and consequent compensation responses, which play a beneficial effect in weight control. A recent study in diabetic rats , however, showed that SG plus trunk vagotomy failed to change body weight, caloric intake, or glucose metabolism compared with SG alone. To explain the paradox, the authors speculated the formation of collateral innervations as well as the regulation of related neural pathways through the visceral nervous system.…”
Section: Mechanisms Of Weight Lossmentioning
confidence: 94%
“…Using a retrograde tracer, Ballsmider et al confirmed that SG induced the damage of the gastric vagal nerve and consequent compensation responses, which play a beneficial effect in weight control. A recent study in diabetic rats , however, showed that SG plus trunk vagotomy failed to change body weight, caloric intake, or glucose metabolism compared with SG alone. To explain the paradox, the authors speculated the formation of collateral innervations as well as the regulation of related neural pathways through the visceral nervous system.…”
Section: Mechanisms Of Weight Lossmentioning
confidence: 94%
“…Actually, truncal vagotomy (TV) was promoted as a weight-loss procedure and resulted in good effects as early as 40 years ago [ 22 , 23 ], although lost focus with the development of SG and Roux-en-Y gastric bypass (RYGB) subsequently. In recent years, with increasing attention of vagus nerve on weight regulating, several studies have reported that TV or SG-TV resulted in drastic reductions of BW [ 24 , 25 ]. However, there is no study reported the effect of TV and TV-related BS on changing of gut microbiota.…”
Section: Introductionmentioning
confidence: 99%